A Case Series of Vaping-Induced Lung Injury in a Community Hospital Setting. (31st January 2020) - Ali, Mohammed; Khan, Kashmala; Buch, Mihir; Ramos- Ramirez, Manuel; Sharma, Munish; Patel, Seema; Choudhury, Saiara; Anjum, Humayun; Khan, Alamgir; Surani, Salim
Abstract : Acute and subacute injury to the lung parenchyma can be caused by multiple products. Over the past few years, vaping (also known as E-cigarettes) has become a popular trend and has been considered "safer" alternative to smoking cigarettes, especially among young adults. The use of E-cigarettes has rapidly increased, and according to the most recent report by CDC released at the end of December 2019, 2, 506 cases and more than 54 associated deaths due to vaping/E-cigarette-associated lung injury were reported. Though vitamin E acetate and tetrahydrocannabinol (THC) have been found in most of the bronchoalveolar lavage samples, there are still small numbers of cases that have not reported to using THC-containing compounds. Research looking into other possible constituents in E-cigarettes that can account for the etiology of disease and effects of vaping as it relates to pulmonary physiology still remains limited and uncertain. We hereby present a case series of 5 patients who were admitted primarily for respiratory symptoms of cough, dyspnea, and fevers and were diagnosed with vaping-induced pulmonary injury.